CHARACTERISTICS AND ALOPECIA ACTIVITY OF PAKIS GAJAH (ANGIOPTERIS EVECTA (G.FORST) HOFFM.) GROWING IN GALUNGGUNG MOUNTAINSIDE, WEST JAVA - Mustarichie, Resmi; Ramdhani, Danni; Iskandar, Yopie (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study aims to determine characteristics and alopecia activity of Pakis Gajah (Angiopteris evecta (G.Forst) Hoffm.) growing in Galunggung mountainside, West Java. Methods: A. evecta was collected, determined and extracted using ethanol 95% by maceration. The extract was characterized based on Farmakope Indonesia method. Phytochemical screening was applied based on Farnsworth's method. Its alopecia activity was determined by Tanaka method on male Angora rabbits. Results: The results showed that A. evecta simplicia had dried shrinkage characteristics of 3.35%; ash content 4.73%; water soluble sari content 20.11%; ethanol soluble concentration 5.94%; density 0.820; pH of extract 5.33; microchemical examination with H2SO4 gives a dark brown color, with 2N NaOH giving a bright yellow color, with the alkaline solution giving fluorescence, with FeCl3 giving a greenish-green color; its chemical contents were polyphenols, flavonoid, steroids, triterpenoids, quinones, monoterpenoid, and sesquiterpenoids. Alopecia activity showed that the water fraction and n-hexane had hair growth stimulating activity and water fraction was the fraction that had the most excellent activity, while ethyl acetate did not have such activities. The alopecia results were compared with minoxidil standards. Conclusion: These results indicated that the water fractions A. evecta had the most alopecia activity on research animal. Our results suggest before it can be used in humans, it is necessary to do further research on the bald volunteers.